Implementation of Minister of Home Regulation Number 17 2016 At The Development Planning, Research and Agency Wajo District Regional Development - Herlina*, Besse; Engka, Rusli; Rahman, Husnah; Hajar, Ibrahim (Universitas Syiah Kuala, 2024)
As part of implementing regional government research and development policies, it can carry out its duties and functions relating to; research, development, study, engineering, implementation, operation and evaluation of policies, hereinafter referred to as main research and development, are scientific activities aimed at generating new understanding/methods and/or developing their practical application in the context of science and technology within the scope of domestic governance. This study aims to determine the implementation of the policy of the Minister of Home Affairs Regulation Number 17 of 2016 and to find out the supporting and inhibiting factors encountered in the implementation of the policy of the Minister of Home Affairs Regulation Number 17 of 2016 at the Wajo Regency Regional Development Planning, Research and Development Agency, using the type of descriptive research with a qualitative approach. The results of this study indicate that, the implementation of the policy of the Minister of Home Affairs Regulation Number 17 of 2016, seen from the aspect of content and context shows an improvement in governance according to the analysis of regional research and development in carrying out regional development planning programs, by looking at an interest, the benefits of the policy making changes by involving responsive resources and strategies by implementing actors to apply the policy, this shows that the basic reference for this regulation can be carried out properly.